2018
DOI: 10.17219/acem/69733
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acid load and cardiometabolic risk in the Polish adult population

Abstract: The dietary acid load in the Polish adult population was relatively low. There was no independent relationship between dietary acid load and cardiovascular disease and its risk factors in the population under study, except for the positive association between the PRAL value and diabetes prevalence in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 18 publications
8
51
0
Order By: Relevance
“…In the study by Akter, no association between PRAL, NEAP and FBS or HbA 1 C was reported. Similar findings were also observed in several other studies . Akter et al reported that men in the highest quartiles of PRAL had 61% higher odds of developing diabetes compared with the lowest quartile; while no association was observed among women.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…In the study by Akter, no association between PRAL, NEAP and FBS or HbA 1 C was reported. Similar findings were also observed in several other studies . Akter et al reported that men in the highest quartiles of PRAL had 61% higher odds of developing diabetes compared with the lowest quartile; while no association was observed among women.…”
Section: Resultssupporting
confidence: 88%
“…While no association among men was reported. Similar findings of the higher prevalence of diabetes or higher odds of diabetes were reported in two other studies . In the study by Kiefte‐de Jong, the odds of T 2 DM in highest quintile of NEAP and PRAL were higher compared with the lowest in NHS and NHS II cohorts while in the HPFS study these associations were not significant.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations